THE PUBLIC ADMINISTRATION OF INVESTMENT ACTIVITY AT THE REGIONAL LEVEL IN UKRAINE: PROBLEMS AND DIRECTIONS OF IMPROVEMENT The - Fedorchak O.V. (Pressing Problems of Public Administration, 2017)
The article considers the essence of the system of public administration of investment activity at the regionallevel in Ukraine. It has been noted that separate functions of management of investment climate at theregional level are distributed between structural subdivisions of local state administrations and executivebodies of local self-government authorities. Part of the function of creating an investment climate is alsocarried out by regional development agencies. However, the cumulative powers of these institutions donot ensure the implementation of a fully- edged investment management process at the regional level.